Bacterial cellulose for advanced medical materials - De Olyveira, Gabriel Molina [UNESP]; Costa, Ligia Maria Manzine; Riccardi, Carla Dos Santos [UNESP]; Santos, Márcio Luiz Dos [UNESP]; Daltro, Paula Braga [UNESP]; Basmaji, Pierre; Daltro, Gildásio De Cerqueira; Guastaldi, Antonio Carlos [UNESP] (My University, 2016)
Bacterial cellulose (BC) has become established as a new biomaterial and can be used in several applied scientific areas, especially for medical devices. In addition, biomedical materials have claimed attention because of the increased interest in tissue engineering materials for wound care and regenerative medicine. The BC bioprocess production can be changed by controlling the fermentation process. It has unique properties that make it an exciting candidate as a medical material: strength, good integration within the host tissue, and flexibility of production in various shapes and sizes. This chapter describes a morphological investigation in human regenerative medicine, stem cell behavior on bacterial cellulose, and recent drug delivery applications for medical applications. It also discusses futures insights and research with bacterial cellulose.
Keywords: Bacterial cellulose (Nanoskin®); Bionanocomposites; Genetic modifications; Medical applications; Regenerative medicine